2014
DOI: 10.1007/s00266-014-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

Saddle-Nose Deformity Repair with Microplate-Adapted Costal Cartilage

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…20 Eren reported warping in 5 out of 5 patients with an unstabilized dorsal strut. 10 Hyun's more extensive study of 45 patients who received autologous or homogenous costal grafts reported a 2% warping rate when one of three cartilage configurations were used. 4 The pi graft borrows from preexisting techniques to correct the saddle nose deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Eren reported warping in 5 out of 5 patients with an unstabilized dorsal strut. 10 Hyun's more extensive study of 45 patients who received autologous or homogenous costal grafts reported a 2% warping rate when one of three cartilage configurations were used. 4 The pi graft borrows from preexisting techniques to correct the saddle nose deformity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Elaborate strategies to prevent warping include harvest of bone graft and reinforcement with Kirschner wires, laminate construction, microplates, chimeric autologous graft, or crossbar grafts. 10,11,13,15,22,23 The authors feel that a simpler approach is to fixate the dorsal strut at a second point. The pi graft was designed with a structural engineer's mindset: the second strut is intended to (1) reduce the moment arm on the nasal-graft junction and (2) provide a third point of fixation, on the opposite side of the caudal strut, to minimize lateral warping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are often treated with cantilevered dorsal grafts of various materials. 6,[15][16][17] However, the main reason for the depression of nasal dorsum is weakening of the septal skeleton, which if not reestablished, cannot produce a functional improvement with a simple onlay graft or a cantilevered dorsal graft.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies focusing on the aesthetic feature of this deformity have contended the need for onlay grafts to restore the normal appearance of the nasal dorsum. Although different materials and the fixation techniques have their own advantages and disadvantages, [3][4][5][6] the absence of addressing septal support has been a major pitfall.…”
mentioning
confidence: 99%